Pathologies caused by disorders of the nervous system of children (Eurasian Journal of Humanities and Social Sciences, 2023)
This article describes the diseases caused by the disruption of the nervous system and its function as a result of normal and abnormal activity of the nervous system in children and the best methods of prevention.